Asthma in Patients with Chronic Kidney Disease Undergoing Dialysis: A Narrative Review - Rifai, Achmad; Nahak, Malisa Sherly Theresia (Universitas Brawijaya, 2026)
Asthma and chronic kidney disease (CKD) are chronic disorders with substantial morbidity and increasingly recognized overlap. This narrative review summarizes the current evidence on the relationship between asthma and CKD, with emphasis on patients undergoing dialysis. Available data indicate that asthma, particularly when severe or poorly controlled, is associated with a higher risk of CKD, whereas CKD more consistently modifies pulmonary physiology and worsens control of pre-existing asthma than clearly causing new-onset asthma. The interaction is supported by several mechanisms, including systemic inflammation, immune dysregulation, endothelial injury, oxidative stress, disordered acid-base balance, and fluid overload. In advanced CKD, anemia, uremia, metabolic disturbances, and volume excess may mimic or aggravate respiratory symptoms, while dialysis adds further complexity through rapid intravascular volume shifts, complement activation, membrane bioincompatibility, and electrolyte changes that can influence lung mechanics and airway reactivity. Management generally follows standard asthma therapy based on inhaled corticosteroids and bronchodilators, but treatment must be individualized according to kidney function, dialysis status, polypharmacy, and the risk of medication-related adverse effects. Careful integration of respiratory assessment, renal monitoring, and volume management is therefore essential in this population.